Prevalence and Associated Factors of Depression among Grade 12 Students Tutoring for University Admission Examination in Tutoring Institutes in Siam Area, Pathumwan District, Bangkok Metropolis - Latthasaksiri, Gunkarin; Roomruangwong, Chutima (Journal of Dhamma for Life, 2025)
This study is aimed to examine the prevalence and associated factors of depression among grade 12 students tutoring for University Admission Examination in tutoring institutes in Siam Area, Pathumwan District, Bangkok Metropolis. This cross-sectional descriptive study was conducted in 115 grade 12 students who were being tutored for University Admission Examination in tutoring institutes in Siam Area, Pathumwan District, Bangkok Metropolis. The data were collected during October 2024 to December 2024 by self-report questionnaires including demographic data questionnaire, perception of parental expectation in University Admission questionnaire, self-expectation in University Admission questionnaire, Center for Epidemiological Studies-Depression Scale: CES-D, Spielberger’s the State-Trait Anxiety Inventory (STAI Form Y-1, A-state), and The Revised version of Thai Rosenberg Self-Esteem Scale: Revised Thai RSES. The data were analyzed by descriptive and inferential statistics. The study found that the prevalence of depression was 29.4%. The factors significantly associated with depression are type of school, impact of Covid-19 pandemic, academic stress from tutoring, having trusted person to console with, peer acceptance, self-expectation for University Admission, anxiety, and self-esteem.